Perancangan Interior Chocolate House di Surabaya - Widya Wijaya; Sriti Mayang Sari; M. Taufan Rizqy (Intra, 2016)
Dense city of Surabaya and the modern wolrd can make people stressed and bored with the routine performed every day. Therefore needed a facility that can provide relaxationto soothe the mind at once pampering after a long day of work. Chocolate house in Surabaya, this is a place that can be used as a means of recreation to relieve boredom, where visitors can also get education by conducting chocolate making courses, as well as see various explanations about cocoa contained in chocolate gallery. Otherwise it can be used as a place fo relaxation to soothe the mind and relieve stress. By taking a refreshing design concept and apply natural impression of the interior rooms were implemented through the use of materials, so that the design of the room can be at one with nature and provide relaxation to the visitors.